MiR-218 Targeted Regulation of Robol Expression Regulates Proliferation, Invasion and Migration of Glioma Cells: MiR-218 and Glioma Cells - Zhang, Rui; Jiang, Wei; Liu, Zhanhui; Hou, Pengfei; Zhang, Shitao (Cellular and Molecular Biology, 2022)
In recent years, more and more researches has focused on "molecular targeted therapy" for basic genes and regulatory cells, but the effect is not ideal. Therefore, the discovery of new molecular targets with diagnostic and therapeutic significance can not only lay a solid foundation for molecular diagnosis and classification of lesions but also contribute to targeted therapy of glioma. This study aimed to discover the molecular mechanism of mir-218 targeting the regulation of robol expression on proliferation, invasion and migration of glioma cells and to provide a theoretical and experimental basis for finding therapeutic targets of glioma. The purpose of this study was to investigate the effect of mir-218 on gliomas by using the method of control experiment. The results showed that the number of gliomas under the action of mir-218 decreased from about 150 to about 80, and the number would tend to a fixed value range over time. In the experiment, the data decreased from about 150 to nearly 20, and compared with the control group, the control of glioma cell proliferation was very excellent.